Transcriptome profiling dataset of different developmental stage flowers of soybean (Glycine max) - Eszter Virág; Géza Hegedűs; Barbara Kutasy; Kincső Decsi (Data in Brief, 2022)
The dynamic of flower development is a key agronomic characteristic affecting soybean yield. RNA-seq dataset of field-cultivated soybean flowers in four developmental stages including flower buds, and early, mature, and overblown stage flowers are reported in this paper. Gene Expression (Gex) library construction and Illumina NextSeq550 sequencing were carried out to produce 86 bp long forward reads. Reads were preprocessed and deposited in the National Center for Biotechnology Information Sequence Read Archive (NCBI SRA) database. These SRA depositions are under the BioProject accession: PRJNA807844. A reference transcriptome dataset was de novo assembled using these SRA reads. Annotation, differential expression, and gene set enrichment analyses were performed and deposited in the Mendeley Data.